(untitled) (Journal of Organizational Psychology, 2022)
Despite advances in understanding narcissism, limited attention has been paid to articulating a higherorder construct that explicitly captures the multi-faceted nature of narcissistic motives and displays. To address this missing link, this study presents an identity-based self-regulatory model of narcissism. We draw from identity control theory (ICT) and propose that dominance identity, a personal identity central to the narcissistic self-concept, is the overarching psychological motive driving narcissistic beliefs and behaviors. Validating, promoting, and protecting this dominance identity is the primary goal that guide narcissistic self-regulatory processes. We identify grandiose self-views, narcissistic self-promotion, and interpersonal aggression as the primary intra-personal and interpersonal strategies employed to sustain narcissistic personal identity. Complementing the prominent self-esteem based regulatory model of narcissism, the central premise of this framework is that dominance identity acts much like a thermostat that sets identity goals. Meanwhile, self-esteem, like a thermometer, is an evaluative indicator of such identity -goal attainment. This identity regulatory model provides a parsimonious way to organize current understanding of the underpinning psychological drivers of narcissism.